Renin-Angiotensin System Blockade Is Renoprotective in Immune Complex–Mediated Glomerulonephritis - Guo, Shunhua (American Society of Nephrology, 2008)
Blockade of the renin-angiotensin system is renoprotective in a variety of chronic nephropathies, but the direct effect of such treatment in active, immune complex–mediated glomerulonephritis is unknown. This study investigated the short- and long-term effects of an angiotensin-converting enzyme inhibitor (enalapril) and an angiotensin II type 1 receptor blocker (losartan) in thymic stromal lymphopoietin transgenic (TSLPtg) mice, which develop mixed cryoglobulinemia and severe cryoglobulinemia-associated membranoproliferative glomerulonephritis. Enalapril and losartan each reduced hypertension, proteinuria, glomerular extracellular matrix deposition, and mesangial cell activation in TSLPtg mice. These renoprotective effects were not observed with hydralazine treatment, despite a similar antihypertensive effect. Treatment with enalapril or losartan also decreased renal plasminogen activator inhibitor-1 in TSLPtg mice, assessed by immunohistochemistry and quantitative real-time reverse transcriptase–PCR. None of the treatments affected immune complex deposition or macrophage infiltration. Overall, enalapril- and losartan-treated TSLPtg mice survived significantly longer than untreated TSLPtg mice. These studies demonstrate that angiotensin blockade may provide renoprotective benefits, independent of its BP-lowering effect, in the treatment of active immune complex–mediated glomerulonephritis.